Interventionelle Therapie von Harnsteinen = Minimally-invasive therapy of urinary stones - Knoll, Thomas; Trojan, Lutz; Häcker, Axel; Michel, Maurice Stephan; Köhrmann, Kai-Uwe; Alken, Peter (Aktuelle Urologie, 2003)
Thieme E-Books & E-Journals